Prevalence and Determinants of Obesity among Elderly in an Urban Area of Bengaluru - T V Sanjay; Arun Kumar DP; M Madhusudan (Medsci Publications, 2017)
Background: Obesity is a serious public health challenge all over the globe. Aging process increases the risk of obesity by bringing about changes in the body composition and innate environment. The present study was undertaken to find out the prevalence and determinants of obesity among elderly population in an urban area. Methods: Data was collected from 247 elderly living in an urban area of Bengaluru, regarding socio-personal characteristics, dietary habits and physical exercise practices. Anthropometric measurements such as height, weight, BMI, waist circumference and body fat percentage by using body fat monitor were recorded. Results: The prevalence of generalised obesity and central obesity was 62.3% and 56.7% respectively and female sex(P=0.03, P=0.02), family history of obesity (P=0.0004, OR=3.6), (P=0.0002, OR=3.6), presence of co-morbidity (P=0.0002, OR=3.1), (P=0.0001, OR=3.7) and eating three or more meals (P=0.004, OR=3.5) (P=0.007, OR=7.1) were significantly associated with both generalised and central obesity. Strong positive correlation of BMI with waist circumference and percentage body fat, and waist circumference with percentage body fat were also observed. Conclusions: Around two third and more than half of the elderly subjects were having obesity. Female sex, family history of obesity, presence of co-morbidities and eating three or more meals were significantly associated with both the type of obesity and BMI, waist circumference and body fat percentage are suitable indicators of assessment of obesity among elderly subjects.